Toward's a holistic corporate framework for creating innovation culture - Wan Ismail, Wan Kamaruzzaman; Abdulmajed, Rahuma (Zhejiang Univ Press, 2007)
Innovation is a complex, multi-dimensional, and multifaceted phenomenon. In general, innovation is an environment or a culture that exists in a company and drives value creation. Thus, inculcating a culture of innovation is a vital requirement to provide the organization with necessary ingredients to innovate. This conceptual paper draws upon a wide and eclectic range of literature in the area of innovation and culture. A number of published works on culture and innovation were critiqued. The findings from this literature review were used to develop a framework illustrating the holistic combination between the cultural aspects and the innovation. This paper emphasizes the importance of the broad framework which illustrates the innovation culture in a one defined term